Thermally conductive pastes, dry films, cured products and electronic components
By adjusting the cured film characteristics and composition of the thermally conductive paste, the problems of low heat dissipation and high visibility of the thermally conductive paste on the solder resist layer are solved, and high adhesion and excellent heat dissipation performance are achieved. It is suitable for electronic components .
Patent Information
- Application Number
- CN202110128733.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-01-29
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2041-01-29
AI Technical Summary
When the conventional thermally conductive paste is applied to the solder resist layer, it leads to low heat dissipation and high visibility, making it difficult to detect defects, and insufficient curing leads to poor adhesion.
By adjusting the absorbance, L value and thermal conductivity of the cured film of the thermally conductive paste, it is ensured that within a specific range, epoxy resins using biphenyl skeleton and dicyclopentadiene skeleton, as well as thermally conductive fillers with different average particle sizes. and colorants to improve adhesion and visibility.
A thermal conductive paste with low visibility, excellent heat dissipation and good adhesion when applied to the solder resist layer is realized, which solves the problems of insufficient curing and insufficient adhesion, and improves the overall performance of electronic components.
Smart Images

Figure BDA0002924816540000161 
Figure BDA0002924816540000171 
Figure HDA0002924816550000011
Abstract
Description
Technical Field
[0001] The invention relates to a thermally conductive paste, a dry film, a cured product and an electronic component. Background Art
[0002] In recent years, with the demand for miniaturization and high performance of electronic devices, the semiconductor chips carried have been increasingly dense and highly functional, and printed circuit boards on which semiconductor chips are mounted have also been sought to be miniaturized and highly dense. As a result, heat dissipation has recently become a major issue as a countermeasure for heat generation in semiconductor chips and printed circuit boards. Therefore, the heat dissipation of printed circuit boards has been improved by using thermally conductive pastes and the like.
[0003] As such a thermally conductive paste, as described in Patent Document 1, a resin composition obtained by filling an epoxy resin with a filler having high heat dissipation properties such as alumina is used.
[0004] Prior art literature
[0005] Patent Literature
[0006] Patent Document 1: Japanese Patent Application Laid-Open No. 2004-10668 Summary of the invention
[0007] Problem that the invention aims to solve
[0008] The present inventors have found that resin layers such as solder resist layers used in printed wiring boards have low heat dissipation properties. Therefore, in order to improve the heat dissipation properties, it is necessary to apply a thermally conductive paste having excellent heat dissipation properties on the resin layer to form a laminate consisting of two layers, thereby improving the heat dissipation properties of the entire printed wiring board.
[0009] However, when the conventional thermal conductive paste is applied on the solder resist layer, if the visibility of the thermal conductive paste is high, the visual unity of the entire substrate is lost, so when a defect occurs on the substrate, the defect is not conspicuous and becomes difficult to find. Therefore, it has been found that it is necessary to reduce the visibility of the coating pattern of the thermal conductive paste.
[0010] In addition, when applying the conventional thermally conductive paste to the solder resist layer, in order to ensure the close adhesion between the solder resist layer and the thermally conductive paste, it is necessary to apply the thermally conductive paste to the semi-cured solder resist layer, cure the thermally conductive paste, and then irradiate the solder resist layer with ultraviolet rays to completely cure the solder resist layer. In such a process, problems such as insufficient curing of the solder resist layer as the base layer and peeling of the thermally conductive paste may occur in the portion where the thermally conductive paste is applied.
[0011] The present invention is made to solve such problems, and its purpose is to provide a thermally conductive paste, a dry film, a cured product thereof, and an electronic component using the same, which can achieve low visibility when applied on a solder resist layer, excellent heat dissipation, and excellent adhesion to the solder resist layer as a base.
[0012] Solutions for solving problems
[0013] As a result of intensive studies, the present inventors have found that all of the above problems can be solved by setting the absorbance, L value, and thermal conductivity of a cured product of a thermally conductive paste to specific ranges, thereby completing the present invention.
[0014] That is, the present invention is as follows.
[0015] [Item 1]
[0016] A thermally conductive paste, comprising (A) a thermosetting component, (B) a thermally conductive filler, and (C) a colorant.
[0017] The amount of the thermally conductive filler (B) blended is 30% by weight or more and 80% by weight or less relative to the total solid content of the thermally conductive paste.
[0018] The thermally conductive paste was heat-cured at 150° C. for 1 hour to obtain a cured film.
[0019] The absorbance of the cured film at a measurement wavelength of 364 nm when the film thickness of the cured film is 10 μm is 0.75 or more and 1.50 or less,
[0020] The L value of the L*a*b colorimetric system when the film thickness of the cured film is 100 μm is 28 or more and 38 or less,
[0021] The thermal conductivity of the cured film when the film thickness is 100 μm is 0.65 W / m·K or more and 3.1 W / m·K or less.
[0022] [Item 2]
[0023] The thermally conductive paste according to item 1, characterized in that it contains an epoxy resin having at least one structure selected from a biphenyl skeleton and a dicyclopentadiene skeleton as the (A) thermosetting component.
[0024] [Item 3]
[0025] The thermally conductive paste according to items 1 and 2, wherein the thermally conductive filler (B) includes two or more thermally conductive fillers having different average particle sizes.
[0026] [Item 4]
[0027] The thermally conductive paste according to any one of items 1 to 3, characterized in that the (B) thermally conductive filler includes a first thermally conductive filler having a small average particle size and a second thermally conductive filler having a large average particle size, and when the average particle size of the first thermally conductive filler is set to 1, the average particle size of the second thermally conductive filler is greater than or equal to 1.5 and less than or equal to 5.0.
[0028] [Item 5]
[0029] The thermally conductive paste according to any one of items 1 to 4, wherein the amount of the (A) thermosetting component blended is 10% by weight or more and 70% by weight or less relative to the total solid content of the thermally conductive paste.
[0030] [Item 6]
[0031] The thermally conductive paste according to any one of items 1 to 5, wherein the amount of the colorant (C) blended is 1% by weight or more and 10% by weight or less relative to the total solid content of the thermally conductive paste.
[0032] [Item 7]
[0033] The thermally conductive paste according to any one of items 1 to 6, further comprising (D) a thermally conductive reinforcing material.
[0034] [Item 8]
[0035] The thermally conductive paste according to item 7, wherein the (D) thermally conductive reinforcing material is in an amount of 0.1 wt % or more and 2.0 wt % or less relative to the total solid content of the thermally conductive paste.
[0036] [Item 9]
[0037] A dry film characterized by comprising a resin layer obtained by applying the thermally conductive paste according to any one of items 1 to 8 onto a film and drying the film.
[0038] [Item 10]
[0039] A cured product characterized in that it is obtained by curing the thermally conductive paste according to any one of items 1 to 8 or the resin layer of the dry film according to item 9.
[0040] [Item 11]
[0041] An electronic component characterized by comprising the cured product according to item 10.
[0042] Effects of the Invention
[0043] According to the present invention, it is possible to provide a thermally conductive paste, a dry film, a cured product thereof, and an electronic component using the same, which have low visibility when applied onto a solder resist layer and are excellent in heat dissipation and adhesion to the solder resist layer as a base. BRIEF DESCRIPTION OF THE DRAWINGS
[0044] Figure 1 This is a diagram showing a substrate used for evaluating adhesion in Examples.
[0045] Description of Reference Numerals
[0046] D fixture
[0047] L1 Adhesive
[0048] L2 Thermally conductive cured product obtained by curing thermally conductive paste
[0049] L3 Solder resist layer obtained by curing the insulating photocurable thermosetting resin composition
[0050] L4 Copper Clad Laminate DETAILED DESCRIPTION
[0051] The present invention is a thermally conductive paste, characterized in that it comprises (A) a thermosetting component, (B) a thermally conductive filler, and (C) a colorant.
[0052] The amount of the thermally conductive filler (B) blended is 30% by weight or more and 80% by weight or less relative to the total solid content of the thermally conductive paste.
[0053] The thermally conductive paste was heat-cured at 150° C. for 1 hour to obtain a cured film.
[0054] The absorbance of the cured film at a measurement wavelength of 364 nm when the film thickness of the cured film is 10 μm is 0.75 or more and 1.50 or less,
[0055] The L value of the L*a*b colorimetric system when the film thickness of the cured film is 100 μm is 28 or more and 38 or less,
[0056] The thermal conductivity of the cured film when the film thickness is 100 μm is 0.65 W / m·K or more and 3.1 W / m·K or less.
[0057] The absorbance at a measured wavelength of 364 nm when the cured film obtained by heat curing the thermal conductive paste of the present invention at 150° C. for 1 hour and having a film thickness of 10 μm must be 0.75 or more and 1.50 or less. When the absorbance exceeds 1.50, the solder resist layer of the base decreases in strength and becomes brittle due to insufficient curing, so that the thermal conductive paste peels off together with the base, and the adhesion becomes insufficient. When the absorbance is less than 0.75, the solder resist layer of the base is overcured, and the adhesion between the solder resist layer of the base and the thermal conductive paste is reduced.
[0058] The upper limit of the absorbance at a measurement wavelength of 364 nm when the film thickness of the cured film is 10 μm is preferably 1.30. The lower limit of the absorbance when the film thickness of the cured film is 10 μm is preferably 0.80.
[0059] The absorbance can be measured by a spectrophotometer, etc., but is not limited thereto. For example, the absorbance can be measured by a method described in detail in the examples below.
[0060] The L value of the L*a*b colorimetric system of the cured film obtained by heat curing the thermal conductive paste of the present invention at 150°C for 1 hour with a film thickness of 100 μm must be 28 or more and 38 or less. By setting the L value to 28 or more, the strength of the thermal conductive paste becomes sufficiently high, so the adhesion between the solder resist layer of the base and the thermal conductive paste is excellent. By setting the L value to 38 or less, the visibility becomes sufficiently low, and there is a sense of visual unity as a whole, so when there is a defect on the substrate, the defect is conspicuous and easy to find.
[0061] The upper limit of the L value of the L*a*b colorimetric system when the film thickness of the cured film is 10 μm is preferably 35, more preferably 34, and particularly preferably 33. The lower limit of the L value of the L*a*b colorimetric system when the film thickness of the cured film is 10 μm is preferably 29.0, and more preferably 29.5.
[0062] The L value of the L*a*b colorimetric system can be measured according to JIS Z 8729, but is not limited thereto. For example, the L value can be measured by the method described in detail in the examples below.
[0063] The thermal conductivity of the cured film obtained by heat curing the thermal conductive paste of the present invention at 150° C. for 1 hour with a film thickness of 100 μm must be 0.65 W / m·K or more and 3.1 W / m·K or less. When the thermal conductivity is higher than 0.65 W / m·K, a thermal conductive paste having excellent heat dissipation can be obtained. When the thermal conductivity is lower than 3.1 W / m·K, the thermal conductive paste has sufficient mechanical strength, so the adhesion with the solder resist layer of the base becomes good.
[0064] The upper limit of the thermal conductivity of the cured film when the film thickness is 100 μm is preferably 3.1 W / m·K, more preferably 2.8 W / m·K. The lower limit of the thermal conductivity of the cured film when the film thickness is 100 μm is preferably 0.7 W / m·K, more preferably 0.8 W / m·K.
[0065] The thermal conductivity can be measured according to ASTM D5470-17, but is not limited thereto. For example, the thermal conductivity can be measured using the method described in detail in the examples below.
[0066] Hereinafter, each component of the thermally conductive paste of the present invention will be described in detail.
[0067] (A) Thermosetting ingredients
[0068] As long as the absorbance of the cured film of the present invention when the film thickness is 10 μm, the L value of the L*a*b colorimetric system when the film thickness is 100 μm, and the thermal conductivity when the film thickness is 100 μm of the cured film are within the prescribed numerical ranges, the (A) thermosetting component contained in the thermally conductive paste of the present invention is not particularly limited, and a thermosetting resin and / or compound generally used in the field of printed circuit boards can be used.
[0069] Examples of the aforementioned (A) thermosetting component include, for example, epoxy resins, episulfide resins, polyurethanes, polyimides, phenolic resins, unsaturated resins, amino resins such as urea resins or melamine resins, carbodiimide resins, bismaleimide resins, cyclocarbonate compounds, oxazine compounds, oxazoline compounds, and other known and commonly used thermosetting resins, etc. The thermosetting components are not particularly limited to these, and may be used alone or in combination of two or more thereof.
[0070] As epoxy resin, representatively, there are compounds having at least 2 epoxy groups in the molecule. Specifically, for example, bisphenol A type epoxy resin, bisphenol F type epoxy resin, hydrogenated bisphenol A type epoxy resin, brominated bisphenol A type epoxy resin, bisphenol S type epoxy resin, phenol novolac type epoxy resin, cresol novolac type epoxy resin, bisphenol novolac type epoxy resin, biphenyl type epoxy resin, naphthol type epoxy resin, naphthalene type epoxy resin, dicyclopentadiene type epoxy resin, dicyclopentadiene novolac type epoxy resin, triphenylmethane type epoxy resin, alicyclic epoxy resin, aliphatic chain epoxy resin, phosphorus-containing epoxy resin, anthracene type epoxy resin, norbornene type epoxy resin, adamantane type epoxy resin, fluorene type epoxy resin, aminophenol type epoxy resin, aminocresol type epoxy resin, alkylphenol type epoxy resin etc. can be used. These epoxy resins can be used alone or in combination of two or more.
[0071] Examples of commercially available products of the thermosetting component (A) include bisphenol A epoxy resins such as EPICLON 840, EPICLON 850, EPICLON 1050, and EPICLON 3050 (manufactured by DIC Corporation), Epikote 828, Epikote 1001, Epikote 1002, and Epikote 1003 (manufactured by Mitsubishi Chemical Corporation), Epotote YD-011, Epotote YD-012, Epotote YD-127, and Epotote YD-128 (manufactured by NIPPON STEEL Chemical & Material Co., Ltd.), Epikote 806 and Epikote 807 (manufactured by Mitsubishi Chemical Corporation), Epotote YDF-170, Epotote YDF-2001, and Epotote YDF-2004 (manufactured by NIPPON STEEL Chemical & Material Co., Ltd.), and Epikote 806 and Epikote 807 (manufactured by Mitsubishi Chemical Corporation). Co., Ltd.), bisphenol F type epoxy resins such as Epiclon 830, Epiclon 835, and Epiclon N-730A (manufactured by DIC Corporation), bisphenol A and F mixtures such as Epotote ZX-1059 (manufactured by NIPPON STEEL Chemical & Material Co., Ltd.), hydrogenated bisphenol A type epoxy resins such as Epikote YX-8000 and Epikote YX-8034 (manufactured by Mitsubishi Chemical Corporation) and Epotote ST-3000 (manufactured by NIPPON STEEL Chemical & Material Co., Ltd.), Epotote YDB-400 (manufactured by NIPPON STEEL Chemical & Material Co., Ltd.),Brominated bisphenol A type epoxy resins such as EPICLON 152 and EPICLON 153 (manufactured by DIC Corporation), aminophenol type epoxy resins such as Epikote 630 (manufactured by Mitsubishi Chemical Corporation) and ELM-100 (manufactured by Sumitomo Chemical Co., Ltd.), alkylphenol type epoxy resins such as EPICLON HP-820 (manufactured by DIC Corporation), bisphenol S type epoxy resins such as EPICLON EXA-1514 (manufactured by DIC Corporation), EPICLON N-770 and EPICLON Phenol novolac type epoxy resins such as N-775 (manufactured by DIC Corporation), EPPN-201H, RE-306 (manufactured by Nippon Kayaku Co., Ltd.), Epikote 152, Epikote 154 (manufactured by Mitsubishi Chemical Corporation), EOCN-102S, EOCN-103S, EOCN-104S (manufactured by Nippon Kayaku Co., Ltd.), Epotote YDCN-701, Epotote YDCN-702, Epotote YDCN-703, Epotote YDCN-704 (manufactured by NIPPON STEEL Chemical & Material Co., Ltd.), cresol novolac type epoxy resins such as Epiclon N-660, Epiclon N-670, Epiclon N-680, Epikote 157S70 (manufactured by Mitsubishi Chemical Corporation), Epiclon Bisphenol novolac type epoxy resins such as N-865 (manufactured by DIC Corporation), biphenyl type epoxy resins such as YX-4000 (manufactured by Mitsubishi Chemical Corporation), NC-3000, NC-3000H (manufactured by Nippon Kayaku Co., Ltd.), naphthalene type epoxy resins such as NC-7000L (manufactured by Nippon Kayaku Co., Ltd.), dicyclopentadiene type epoxy resins such as Epiclon HP-7200 (manufactured by DIC Corporation) and XD-1000 (manufactured by Nippon Kayaku Co., Ltd.), triphenylmethane type epoxy resins such as EPPN-501H, 502H (manufactured by Nippon Kayaku Co., Ltd.), 1031S (manufactured by Mitsubishi Chemical Corporation), and Epiclon HP-5000 (manufactured by DIC Corporation), etc.
[0072] From the viewpoint of improving the adhesion with the solder mask, the aforementioned (A) thermosetting component preferably includes an epoxy resin having any one or more structures selected from a biphenyl skeleton and a dicyclopentadiene skeleton. When using an epoxy resin with a biphenyl skeleton, the compatibility of the interface becomes good and the adhesion improves. When using an epoxy resin with a dicyclopentadiene skeleton, the coating strength increases, so it is possible to prevent the coating from rupturing and peeling off. The aforementioned (A) thermosetting component more preferably includes any one or more resins selected from the group consisting of a biphenylphenol novolac type epoxy resin and a dicyclopentadiene novolac type epoxy resin.
[0073] The amount of the thermosetting component (A) is not particularly limited, but is preferably 10% by weight or more, more preferably 18% by weight or more, further preferably 25% by weight or more, preferably 70% by weight or less, and more preferably 65% by weight or less. By setting the amount to 10% by weight or more, the adhesion to the solder resist layer of the base can be improved, and by setting it to 70% by weight or less, a thermally conductive filler can be added in an appropriate ratio, thereby improving heat dissipation.
[0074] (B) Thermally conductive fillers
[0075] The thermally conductive filler (B) contained in the thermally conductive paste of the present invention is not particularly limited, and may be a thermally conductive filler commonly used in the field of printed circuit boards, as long as the absorbance at a measurement wavelength of 364 nm when the cured film has a film thickness of 10 μm, the L value of the L*a*b colorimetric system when the cured film has a film thickness of 100 μm, and the thermal conductivity when the cured film has a film thickness of 100 μm are within the prescribed numerical ranges.
[0076] As the thermally conductive filler (B), a thermally conductive filler composed of a metal oxide or a non-metal oxide having a thermal conductivity of 20 W / m·K or more and less than 55 W / m·K can be used, for example, aluminum oxide, magnesium oxide, zinc oxide, etc. Among these, aluminum oxide is preferred because it is not easy to absorb moisture in the environment and is low-cost.
[0077] The amount of the thermally conductive filler (B) must be 30% by weight or more and 80% by weight or less relative to the total solid content of the thermally conductive paste of the present invention. The upper limit of the amount of the thermally conductive filler (B) is preferably 75% by weight or less, more preferably 70% by weight or less. When it is less than the above range, the thermal conductivity of the cured film and the adhesion to the solder mask layer are reduced, so it is not preferred. On the other hand, when it is more than the above range, the thermal conductivity of the cured film becomes higher, but the appearance such as flatness deteriorates, and the adhesion to the solder mask layer is reduced, so it is not preferred.
[0078] Since a heat sink or the like will be connected to the thermally conductive paste, flatness is required. From the viewpoint that the flatness of the cured film is improved due to the decrease in the viscosity of the thermally conductive paste, the aforementioned (B) thermally conductive filler preferably includes two or more thermally conductive fillers with different average particle sizes. More preferably, the aforementioned (B) thermally conductive filler includes a first thermally conductive filler with a small average particle size and a second thermally conductive filler with a large average particle size. When the average particle size of the aforementioned first thermally conductive filler is set to 1, the average particle size of the aforementioned second thermally conductive filler is preferably 1.5 or more, more preferably 1.8 or more, and further preferably 2.0 or more, preferably 5.0 or less, more preferably 4.0 or less, and further preferably 3.0 or less. In addition, the average particle size of the aforementioned first thermally conductive filler is preferably 0.5 μm or more, more preferably 1 μm or more, preferably 7.5 μm or less, and more preferably 6 μm or less. In the present invention, the average particle size refers to the average primary particle size. The average particle size can be measured by a laser diffraction / scattering method.
[0079] The content of the first thermally conductive filler is preferably less than 40% by weight, more preferably less than 25% by weight, and even more preferably less than 15% by weight of the total thermally conductive filler (B). When the content of the first thermally conductive filler is less than 40% by weight, the dispersibility of the thermally conductive filler in the thermally conductive paste is improved.
[0080] (C) Colorant
[0081] The (C) colorant contained in the thermally conductive paste of the present invention is not particularly limited, and may be a colorant commonly used in the field of printed circuit boards, as long as the absorbance at a measurement wavelength of 364 nm when the cured film has a film thickness of 10 μm, the L value of the L*a*b colorimetric system when the cured film has a film thickness of 100 μm, and the thermal conductivity when the cured film has a film thickness of 100 μm are within the prescribed numerical ranges.
[0082] As the colorant (C), a known and commonly used black pigment can be used, specifically, carbon black, titanium black, iron oxide, cobalt oxide, perylene-based black colorants, etc. These colorants can be used alone or in combination of two or more.
[0083] (C) The colorant may be any combination selected from a combination of a yellow colorant and a purple colorant, a combination of a yellow colorant, a blue colorant and a red colorant, a combination of a green colorant and a purple colorant, a combination of a green colorant and a red colorant, a combination of a yellow colorant, a purple colorant and a blue colorant, and a combination of a green colorant, a red colorant and a blue colorant, and by using this combination, the L value of the L*a*b colorimetric system when the film thickness of the cured film of the thermal conductive paste is 100 μm is set to a predetermined range.
[0084] Among these, it is particularly preferred to include a combination of a yellow colorant, a blue colorant and a red colorant. The amount of the blue colorant is preferably more than 5% by mass, more preferably more than 10% by mass, preferably less than 25% by mass, and more preferably less than 20% by mass relative to the solid content of the yellow colorant. In addition, the amount of the red colorant is preferably more than 20% by mass, more preferably more than 25% by mass, preferably less than 45% by mass, and more preferably less than 40% by mass relative to the solid content of the yellow colorant. In addition, black pigment, purple colorant, orange colorant, brown colorant, etc. can also be combined.
[0085] As blue colorants, there are phthalocyanine-based and anthraquinone-based colorants, and there are compounds classified as pigments and solvents. In addition, metal-substituted or unsubstituted phthalocyanine compounds can also be used.
[0086] Examples of the red colorant include monoazo colorants, disazo colorants, azo lake colorants, benzimidazolone colorants, perylene colorants, diketopyrrolopyrrole colorants, condensed azo colorants, anthraquinone colorants, and quinacridone colorants.
[0087] Examples of yellow colorants include monoazo colorants, disazo colorants, condensed azo colorants, benzimidazolone colorants, isoindolinone colorants, and anthraquinone colorants.
[0088] Green colorants include phthalocyanine-based and anthraquinone-based colorants, etc. In addition, metal-substituted or unsubstituted phthalocyanine compounds may also be used.
[0089] Specific examples of the purple colorant, orange colorant, and brown colorant include Pigment Violet 19, 23, 29, 32, 36, 38, and 42; Solvent Violet 13 and 36; CI Pigment Orange 1, CI Pigment Orange 5, CI Pigment Orange 13, CI Pigment Orange 14, CI Pigment Orange 16, CI Pigment Orange 17, CI Pigment Orange 24, CI Pigment Orange 34, CI Pigment Orange 36, CI Pigment Orange 38, CI Pigment Orange 40, CI Pigment Orange 43, CI Pigment Orange 46, CI Pigment Orange 49, CI Pigment Orange 51, CI Pigment Orange 61, CI Pigment Orange 63, CI Pigment Orange 64, CI Pigment Orange 71, and CI Pigment Orange 73; CI Pigment Brown 23 and CI Pigment Brown 25; CI Pigment Black 1 and CI Pigment Black 7.
[0090] The amount of the colorant (C) blended is not particularly limited as long as the absorbance at a measurement wavelength of 364 nm when the film thickness of the cured film is 10 μm, the L value of the L*a*b colorimetric system when the film thickness of the cured film is 100 μm, and the thermal conductivity when the film thickness of the cured film is 100 μm are within the specified numerical range of the thermally conductive paste. It is preferably 1% by weight or more, more preferably 2% by weight or more, preferably 10% by weight or less, more preferably 8% by weight or less, and particularly preferably 6% by weight or less relative to the total solid content of the thermally conductive paste of the present invention. When the blending amount is 1% by weight or more, the pattern visibility of the thermally conductive paste is reduced, and it becomes easier to find defects. On the other hand, when the blending amount is 10% by weight or less, it becomes easier to control the absorbance and improve the adhesion.
[0091] Other Ingredients
[0092] The thermally conductive paste of the present invention may further contain components other than the above (A) to (C) as long as the absorbance at a measurement wavelength of 364 nm when the cured film has a film thickness of 10 μm, the L value of the L*a*b colorimetric system when the cured film has a film thickness of 100 μm, and the thermal conductivity when the cured film has a film thickness of 100 μm are within the prescribed numerical ranges.
[0093] The thermally conductive paste of the present invention may further include a thermally conductive reinforcing material (D) in addition to the thermally conductive filler (B). The thermally conductive reinforcing material (D) is not particularly limited, but is defined as a filler different from the thermally conductive filler (B) in order to distinguish it from the thermally conductive filler (B).
[0094] As the aforementioned (D) thermally conductive reinforcing material, a thermally conductive material having a thermal conductivity of 60 W / m·K or more can be used representatively, examples of which include metals such as silver and copper, carbon fibers, graphite, graphene and other carbon-based materials, boron nitride, aluminum nitride, etc., preferably carbon nanotubes, aluminum nitride fibers, etc.
[0095] By including the aforementioned (D) thermally conductive reinforcing material, the thermal conductivity is maintained without reducing the content of the thermally conductive filler, so that the adhesion and flatness are improved. Regarding the compounding amount of the aforementioned (D) thermally conductive reinforcing material, in terms of solid content, relative to the total solid content of the thermally conductive paste of the present invention, for example, it is 0.05% by weight or more, preferably 0.1% by weight or more, for example, 2.0% by weight or less, preferably 1.8% by weight or less, and more preferably 1.5% by weight or less. When the compounding amount of the aforementioned (D) thermally conductive reinforcing material is 0.05% by weight or more, the thermal conductivity is further improved. When the solid component compounding amount of the aforementioned (D) thermally conductive reinforcing material is 2.0% by weight or less, a thermally conductive paste having excellent thermal conductivity and flatness can be obtained.
[0096] The thermally conductive paste of the present invention may further contain (E) a heat curing catalyst. Examples of such heat curing catalysts include imidazole derivatives such as imidazole, 2-methylimidazole, 2-ethylimidazole, 2-ethyl-4-methylimidazole, 2-phenylimidazole, 4-phenylimidazole, 1-cyanoethyl-2-phenylimidazole, and 1-(2-cyanoethyl)-2-ethyl-4-methylimidazole; amine compounds such as dicyandiamide, benzyldimethylamine, 4-(dimethylamino)-N,N-dimethylbenzylamine, 4-methoxy-N,N-dimethylbenzylamine, and 4-methyl-N,N-dimethylbenzylamine; hydrazine compounds such as adipic acid dihydrazide and sebacic acid dihydrazide; phosphine compounds such as triphenylphosphine, and commercially available products include 2MZ-A, 2MZ-OK, 2PHZ, 2P4BHZ, 2P4MHZ (all trade names of imidazole compounds), and SAN-APRO manufactured by Shikoku Chemical Industry Co., Ltd. LTD. U-CAT (registered trademark) 3503N, U-CAT3502T (all are trade names of blocked isocyanate compounds of dimethylamine), DBU, DBN, U-CATSA102, U-CAT5002 (all are bicyclic amidine compounds and their salts), etc. It is not particularly limited to these, and can be used alone or mixed with two or more. In addition, guanamine, methylguanamine, benzoguanamine, melamine, 2,4-diamino-6-methacryloyloxyethyl-s-triazine, 2-vinyl-2,4-diamino-s-triazine, 2-vinyl-4,6-diamino-s-triazine-isocyanuric acid adduct, 2,4-diamino-6-methacryloyloxyethyl-s-triazine-isocyanuric acid adduct and other s-triazine derivatives can also be used. It is preferred that these compounds that also function as adhesion imparting agents are used in combination with the aforementioned thermosetting catalyst.
[0097] The amount of these thermosetting catalysts added is sufficient in a normal amount ratio, for example, preferably 0.1 parts by mass or more, more preferably 0.5 parts by mass or more, and preferably 20 parts by mass or less, more preferably 15.0 parts by mass or less, relative to 100 parts by mass of the thermosetting component (A) described above.
[0098] The aforementioned thermal curing catalysts may be used alone or in combination of two or more.
[0099] Furthermore, the thermally conductive paste of the present invention may contain (F) a solvent for the preparation of the paste and the adjustment of viscosity. Examples of the solvent include organic solvents such as ketones, aromatic hydrocarbons, glycol ethers, glycol ether acetates, esters, alcohols, aliphatic hydrocarbons, and petroleum-based solvents, and water. More specifically, ketones such as methyl ethyl ketone and cyclohexanone; aromatic hydrocarbons such as toluene, xylene and tetramethylbenzene; glycol ethers such as cellosolve, methyl cellosolve, butyl cellosolve, carbitol, methyl carbitol, butyl carbitol, propylene glycol monomethyl ether, dipropylene glycol monomethyl ether, dipropylene glycol diethyl ether and triethylene glycol monoethyl ether; esters such as ethyl acetate, butyl acetate, dipropylene glycol methyl ether acetate, propylene glycol methyl ether acetate, propylene glycol ethyl ether acetate and propylene glycol butyl ether acetate; alcohols such as ethanol, propanol, ethylene glycol and propylene glycol; aliphatic hydrocarbons such as octane and decane; petroleum solvents such as petroleum ether, naphtha, hydrogenated naphtha and solvent naphtha, etc.
[0100] These solvents may be used alone or in admixture of two or more.
[0101] The thermally conductive paste of the present invention may further contain known and commonly used additives such as finely powdered silica, organic bentonite, montmorillonite and the like, silicone-based, fluorine-based, polymer-based and the like defoaming agents and / or leveling agents, imidazole-based, thiazole-based, triazole-based and the like silane coupling agents, antioxidants, rust inhibitors, light stabilizers, dispersants and the like, as needed.
[0102] The thermally conductive paste of the present invention may also be in the form of a dry film, the dry film comprising a carrier film (support) and a layer formed on the carrier film and composed of the thermally conductive paste. Therefore, another embodiment of the present invention provides a dry film having a resin layer obtained by applying the thermally conductive paste on a film and drying it.
[0103] When forming a dry film, the thermally conductive paste of the present invention is diluted with the aforementioned solvent and adjusted to an appropriate viscosity, and is applied to a film, especially a carrier film, with a notch wheel coater, a knife coater, a lip coater, a rod coater, an extrusion coater, a reverse coater, a transfer roll coater, a gravure coater, a spray coater, etc., with a uniform thickness, and is usually dried at a temperature of 50 to 130° C. for 1 to 30 minutes to form a resin layer as a dry coating film. The resin layer is not particularly limited, and is usually appropriately selected within the range of preferably 10 μm or more, more preferably 20 μm or more, and preferably 300 μm or less, more preferably 200 μm or less in terms of the film thickness after drying.
[0104] As the carrier film, a plastic film is used, preferably a polyester film such as polyethylene terephthalate, a polyimide film, a polyamide-imide film, a polypropylene film, a polystyrene film, etc. The thickness of the carrier film is not particularly limited, and is usually appropriately selected within the range of 10 μm to 150 μm.
[0105] At this time, after the resin layer is formed on the carrier film, it is preferred to further laminate a peelable cover film on the surface of the resin layer for the purpose of preventing dust from adhering to the surface of the resin layer, etc. As the peelable cover film, for example, a polyethylene film, a polytetrafluoroethylene film, a polypropylene film, a surface-treated paper, etc. can be used, and when peeling the cover film, the adhesion between the resin layer and the cover film is smaller than the adhesion between the resin layer and the carrier film.
[0106] Another aspect of the present invention provides a cured product obtained from the thermally conductive paste or a dry film thereof.
[0107] The thermally conductive paste of the present invention is adjusted to a viscosity suitable for the coating method as required, and is applied to a printed circuit board having a circuit formed thereon by a method such as screen printing, curtain coating, spray coating, or roll coating, and the solvent contained in the composition is volatilized and dried at a temperature of, for example, 60 to 100° C. as required, thereby forming a non-sticky coating film. The obtained coating film or the resin layer of the dry film is then heated to a temperature of, for example, 140 to 180° C. to be thermally cured, thereby obtaining a cured product having low visibility, excellent heat dissipation, and excellent adhesion to the substrate.
[0108] The heating for volatilization drying and heat curing after coating the thermally conductive paste of the present invention can be performed using a hot air circulation drying furnace, an IR furnace, a hot plate, a convection oven, etc. (a method using a device with a heat source having a steam-based air heating method, a method of making the hot air in the dryer contact by convection; and a method of blowing toward the support body using a nozzle).
[0109] Another aspect of the present invention provides an electronic component having the above-mentioned cured product. Such an electronic component is used, for example, in a backlight of a liquid crystal display of a portable terminal, a personal computer, a television, or the like, or a light-emitting element such as an LED.
[0110] Example
[0111] The present invention will be specifically described below by showing examples and comparative examples, but the present invention is not limited to the following examples. It should be noted that the following "parts" and "%" are based on mass unless otherwise specified.
[0112] The components shown in Table 1 and Table 2 were mixed at the mixing ratios (based on mass) of the solid content shown in Table 1 to obtain thermally conductive pastes of Examples 1 to 11 and Comparative Examples 1 to 8.
[0113] [Table 1]
[0114]
[0115] [Table 2]
[0116]
[0117] The details of each component shown in Table 1 and Table 2 are as follows.
[0118] A-1 NIPPON STEEL Chemical & Material Co., Ltd. YD127, bisphenol A type epoxy resin
[0119] A-2 NIPPON STEEL Chemical & Material Co., Ltd. YDF170, bisphenol F type epoxy resin
[0120] A-3 EPICLON N-770 manufactured by DIC Corporation, o-phenol novolac type epoxy resin
[0121] A-4 NC-3000H manufactured by Nippon Kayaku Co., Ltd., biphenol novolac type epoxy resin (epoxy resin having a biphenyl skeleton)
[0122] A-5 HP7200 manufactured by DIC Corporation, dicyclopentadiene novolac type epoxy resin
[0123] B-1 DAW-05 manufactured by Denki Kagaku Kogyo Co., Ltd., Al2O3 (average particle size 5 μm)
[0124] B-2 AS-40 manufactured by Showa Denko K.K., Al2O3 (average particle size 12 μm)
[0125] C-1 Lumogen Yellow S0795 manufactured by BASF JAPAN LTD, yellow colorant
[0126] C-2 Phthalocyanine Blue, Blue Colorant
[0127] C-3 Pigment Red 246, Red Colorant
[0128] C-4 MA-100 manufactured by Mitsubishi Chemical Corporation, carbon black
[0129] D-1 Carbon nanotube 5% dispersion liquid manufactured by TOYOCOLOR CO., LTD., carbon nanotube (the compounding amount in Table 1 and Table 2 indicates the solid content)
[0130] E-1 2MZ-A manufactured by Shikoku Chemical Industry Co., Ltd., imidazole compound
[0131] F-1 Propylene glycol methyl ether acetate (PGMEA), solvent
[0132] Characteristic test
[0133] 1) Color evaluation
[0134] The thermally conductive pastes of Examples 1 to 11 and Comparative Examples 1 to 8 were respectively applied to the entire surface of the copper-clad laminated board that had been subjected to a pre-polishing treatment by screen printing, and thermally cured for 1 hour at 150° C. in a heat circulation drying oven to obtain a cured coating film of about 100 μm. The obtained cured coating film was measured for the value of the L*a*b colorimetric system on copper based on the SCI method using a spectrophotometer (CM-2600d manufactured by Konica Minolta, Inc.), and the L value as an index representing brightness is shown in Tables 1 and 2.
[0135] 2) Absorbance
[0136] After the thermally conductive pastes of Examples 1 to 11 and Comparative Examples 1 to 8 were applied to a glass plate with an applicator, they were heat cured at 150°C for 1 hour in a heat cycle drying oven to obtain a cured coating. Using an ultraviolet visible spectrophotometer Ubest-V-570DS (manufactured by JASCO Corporation) and an integrating sphere device ISN-470 (manufactured by JASCO Corporation), the absorbance baseline at 900 to 300 nm was measured with a glass plate identical to the above-mentioned glass plate. The absorbance of the prepared glass plate with a cured coating was measured, and the absorbance of the cured coating was calculated from the baseline to obtain the absorbance at the target wavelength of 364 nm. In order to prevent the deviation of the absorbance caused by the deviation of the coating film thickness, this operation was performed for two film thicknesses of 8 μm and 12 μm, and a curve of the cured film thickness and the absorbance at 364 nm was prepared, and the absorbance at a film thickness of 10 μm was calculated from the approximate formula passing through its origin.
[0137] 3) Flatness
[0138] The thermally conductive pastes of Examples 1 to 11 and Comparative Examples 1 to 8 were applied by screen printing to the entire surface of a substrate having a comb-tooth copper wiring circuit with a copper thickness of 18 μm and L / S = 0.318 mm / 0.318 mm so that the thickness was 50 μm, and thermally cured at 150° C. for 1 hour in a hot air circulation drying oven to prepare a flatness evaluation substrate. For each cured substrate, the surface roughness of the cured film in the direction perpendicular to the comb-tooth copper wiring was measured within a range of 30 mm in length using a contact type surface roughness measuring device (SE-300, manufactured by Kosaka Laboratory Co., Ltd.). The evaluation criteria are as follows.
[0139] ◎: On the comb-tooth circuit, the maximum tolerance of the concavity and convexity is less than 1μm.
[0140] ○: On the comb-tooth circuit, the maximum tolerance of the concavity and convexity is greater than 1 μm and less than 3 μm.
[0141] △: On the comb-tooth circuit, the maximum tolerance of the concavity and convexity is 3 μm or more.
[0142] 4) Sealing force
[0143] The thermally conductive pastes (equivalent to Figure 1 L2) is applied to the entire surface by screen printing so that the following photosensitive thermosetting resin composition (equivalent to Figure 1 L3) The cured coating film obtained by curing under the following curing conditions is cured to a thickness of 25 μm, and is thermally cured at 150° C. for 1 hour in a heat circulation drying oven.
[0144] The composition of the photosensitive thermosetting resin composition for the base layer is as follows: 90 g of LMP-100 talc (manufactured by FUJI TALC INDUSTRIAL CO., LTD.), 10 g of KAYACURE DPHA (manufactured by Nippon Kayaku Co., Ltd., dipentaerythritol hexa(meth)acrylate), 10 g of Omnirad TPO (manufactured by IGM Resins Co., Ltd., 2,4,6-trimethylbenzoyldiphenylphosphine oxide), 40 g of RE-306 (manufactured by Nippon Kayaku Co., Ltd., phenol novolac type epoxy resin), 1 g of MA-100 manufactured by Mitsubishi Chemical Corporation, 3 g of POLYFLOW No.90 manufactured by Kyoeisha Chemical Co., Ltd., and 15 g of Solvesso 150 (manufactured by Showa Chemical Industry Co., Ltd.), relative to 155 g of the carboxyl group-containing resin varnish synthesized by the following synthesis method.
[0145] <Synthesis Example: Preparation of carboxyl group-containing resin varnish>
[0146] 220 parts by mass (1 equivalent) of cresol novolac epoxy resin (manufactured by Nippon Kayaku Co., Ltd., EOCN-104S, epoxy equivalent 220 g / eq), 140.1 parts by mass of carbitol acetate and 60.3 parts by mass of solvent naphtha were placed in a flask, heated to 90°C and stirred to dissolve. The resulting solution was temporarily cooled to 60°C, 72 parts by mass (1 mol) of acrylic acid, 0.5 parts by mass of methylhydroquinone and 2 parts by mass of triphenylphosphine were added, heated to 100°C and reacted for about 12 hours to obtain a reactant having an acid value of 0.2 mgKOH / g. 80.6 parts by mass (0.53 mol) of tetrahydrophthalic anhydride was added thereto, heated to 90°C and reacted for about 6 hours to obtain a carboxyl-containing resin varnish having a solid content acid value of 85 mgKOH / g and a solid content concentration of 65.8%.
[0147] Base curing conditions: The above-mentioned photosensitive thermosetting resin composition was applied to the entire surface of the copper foil laminate by screen printing to a thickness of 25 μm, and dried in a hot air circulation drying oven at 80°C for 30 minutes. After cooling to room temperature, an exposure device equipped with a high-pressure mercury lamp was used at 400 mJ / cm 2After the entire surface was exposed, a curing treatment was performed in a hot air circulation drying oven at 150° C. for 1 hour.
[0148] After the thermal curing treatment of the thermal conductive paste coating, these substrates were subjected to a UV conveyor furnace at 2000 mJ / cm 2 Expose to ultraviolet light to produce a substrate for adhesion evaluation. Figure 1 As shown, a jig was fixed to a substrate for adhesion evaluation with an adhesive (2082C manufactured by Three Bond, curing conditions: 120° C. for 60 minutes), and the peel strength of the jig was measured under the following conditions using PosiTest AT-A manufactured by DeFelsko.
[0149] Test fixture size: Φ10mm, test speed: 1.0MPa / sec, test environment: 25℃
[0150] The obtained results were evaluated as follows.
[0151] ◎: greater than 5.5MPa
[0152] ○: greater than 4.5MPa and less than 5.5MPa
[0153] △: greater than 3.5MPa and less than 4.5MPa
[0154] ×: 3.5MPa or less
[0155] After the peel strength was measured under the above conditions, the failure mode of the substrate was evaluated as follows.
[0156] Failure mode 1: Interface failure between L2 and L3 layers
[0157] Failure mode 2: Cohesive failure occurs within the L3 layer
[0158] Failure mode 3: Cohesive failure occurs within the L2 layer
[0159] 5) Thermal conductivity
[0160] After the thermally conductive pastes of Examples 1 to 11 and Comparative Examples 1 to 8 were respectively applied to the polyimide film by screen printing, they were dried at 80°C for 15 minutes in a heat circulation drying furnace to obtain a dry coating with a film thickness of 25 μm after drying. Next, the printing on the dry coating was repeated 3 times under the same conditions to obtain a dry coating with sufficient thickness, and a hot air circulation drying furnace was used to perform a heat curing treatment at 150°C for 1 hour, and the obtained cured coating was peeled off from the polyimide film to obtain a cured coating with a film thickness of 100 μm after curing for thermal conductivity measurement. Using the obtained coating, the thermal conductivity was measured by the steady-state method according to ASTMD5470-17. Specifically, a thermal resistance measuring device (L9389 manufactured by Long Win Science and Technology Co., Ltd.) was used to clamp each resin composition with a cooling plate and a heater, and the thermal conductivity was measured by the change in the temperature difference between the upper and lower parts. The results obtained were evaluated as described below.
[0161] ◎: greater than 1.5W / m·K
[0162] ○: 0.65W / m·K or more and 1.5W / m·K or less
[0163] ×: less than 0.65W / m·K
[0164] 6) Visibility of thermal conductive paste pattern
[0165] A comb pattern of L / S = 0.318 mm / 0.318 mm was printed by screen printing on a cured coating film obtained by curing the following photosensitive thermosetting resin composition under the following curing conditions using the thermally conductive pastes of Examples 1 to 11 and Comparative Examples 1 to 8 so as to have a thickness of 25 μm, and a heat curing treatment was performed at 150° C. for 1 hour in a heat circulation drying oven.
[0166] The composition of the photosensitive thermosetting resin composition for the base layer is as follows: 90 g of LMP-100 talc (manufactured by Fuji Talc Co., Ltd.), 10 g of KAYACURE DPHA (manufactured by Nippon Kayaku Co., Ltd., dipentaerythritol hexa(meth)acrylate), 10 g of Omnirad TPO (manufactured by IGM Resins Co., Ltd., 2,4,6-trimethylbenzoyldiphenylphosphine oxide), 40 g of RE-306 (manufactured by Nippon Kayaku Co., Ltd., phenol novolac type epoxy resin), 1 g of MA-100 manufactured by Mitsubishi Chemical Corporation, 3 g of POLYFLOW No.90 manufactured by Kyoeisha Chemical Co., Ltd., and 15 g of Solvesso 150 (manufactured by Showa Chemical Industry Co., Ltd.), relative to 155 g of the carboxyl group-containing resin varnish synthesized by the following synthesis method.
[0167] <Synthesis Example: Preparation of carboxyl group-containing resin varnish>
[0168] 220 parts by mass (1 equivalent) of cresol novolac epoxy resin (manufactured by Nippon Kayaku Co., Ltd., EOCN-104S, epoxy equivalent 220 g / eq), 140.1 parts by mass of carbitol acetate and 60.3 parts by mass of solvent naphtha were placed in a flask, heated to 90°C and stirred to dissolve. The resulting solution was temporarily cooled to 60°C, 72 parts by mass (1 mol) of acrylic acid, 0.5 parts by mass of methylhydroquinone and 2 parts by mass of triphenylphosphine were added, heated to 100°C and reacted for about 12 hours to obtain a reactant having an acid value of 0.2 mgKOH / g. 80.6 parts by mass (0.53 mol) of tetrahydrophthalic anhydride was added thereto, heated to 90°C and reacted for about 6 hours to obtain a carboxyl-containing resin varnish having a solid content acid value of 85 mgKOH / g and a solid content concentration of 65.8%.
[0169] Base curing conditions: The above-mentioned photosensitive thermosetting resin composition was applied to the entire surface of the copper foil laminate by screen printing to a thickness of 25 μm, and dried in a hot air circulation drying oven at 80°C for 30 minutes. After cooling to room temperature, an exposure device equipped with a high-pressure mercury lamp was used at 400 mJ / cm 2 After the entire surface was exposed, a curing treatment was performed in a hot air circulation drying oven at 150° C. for 60 minutes.
[0170] The comb-tooth pattern was observed from a position 30 cm vertically away from the obtained substrate and evaluated as follows.
[0171] ○: Cannot see the pattern
[0172] ×: The pattern can be seen
[0173] As is apparent from Tables 1 and 2, the amount of the thermally conductive filler (B) blended is 30% by weight or more and 80% by weight or less relative to the total solid content of the thermally conductive paste, the cured film obtained by heat curing the thermally conductive paste at 150°C for 1 hour has an absorbance of 0.75 or more and 1.50 or less when the film thickness is 10 μm, the L value of the L*a*b colorimetric system when the film thickness is 100 μm is 28 or more and 38 or less, and the thermal conductivity when the film thickness is 100 μm is 0.65 W / m·K or more and 3.1 W / m·K or less. In Examples 1 to 11, the pattern of the thermally conductive paste is difficult to see, and the evaluation of flatness, thermal conductivity, and adhesion all achieves excellent structures. It should be noted that in Examples 2 and 3, in which an epoxy resin having any one or more structures selected from a biphenyl skeleton and a dicyclopentadiene skeleton is used as the (A) thermosetting component, the evaluation of adhesion achieves even better results. In Example 4, which used two types of thermally conductive fillers with different average particle sizes as the (B) thermally conductive filler, a more excellent result was obtained in the evaluation of flatness. In Example 11, which further included carbon nanotubes as the (D) thermally conductive reinforcing material, a more excellent result was obtained in the evaluation of flatness.
[0174] In contrast, Comparative Example 1, in which the absorbance was less than 0.75 when the film thickness was 10 μm, Comparative Example 2, in which the absorbance exceeded 1.50, and Comparative Example 3, in which the L value of the L*a*b colorimetric system was less than 28 when the film thickness was 100 μm, all obtained poor adhesion results. In Comparative Example 1, the base solder resist layer was over-cured, so the adhesion with the base became insufficient, and peeling occurred at the interface. In Comparative Example 2, the light transmittance was poor, so the base solder resist layer was insufficiently cured and the strength was insufficient, and peeling occurred together with the base, and the adhesion became insufficient. In Comparative Example 3, the curing reaction of the base solder resist layer proceeded appropriately, but the thermal conductive paste of the upper layer was brittle, so cohesive failure occurred in the thermal conductive paste layer, and the result was insufficient adhesion. Comparative Example 4, in which the L value of the L*a*b colorimetric system exceeded 38 when the film thickness was 100 μm, obtained a result that the pattern of the thermal conductive paste could be seen. In Comparative Example 5, in which the thermal conductivity was less than 0.65 W / m·K when the film thickness was 100 μm, the evaluation of thermal conductivity obtained a poor result. In Comparative Example 6, in which the thermal conductivity exceeded 3.1 W / m·K, the thermally conductive paste was brittle, so cohesive failure occurred in the thermally conductive paste layer, resulting in insufficient adhesion. (B) In Comparative Example 7, in which the blending amount of the thermally conductive filler was less than 30 wt%, the evaluation of thermal conductivity obtained a poor result, and since the absorbance was less than 0.75 when the film thickness was 10 μm, the adhesion obtained a poor result. (B) In Comparative Example 8, in which the blending amount of the thermally conductive filler exceeded 80 wt%, the evaluation of flatness obtained a poor result, and since the absorbance was more than 1.50 when the film thickness was 10 μm, the adhesion obtained a poor result.
[0175] These results show that the thermally conductive paste of the present invention can form a cured product with low visibility, excellent heat dissipation and adhesion to the substrate when applied on a solder resist layer. The thermally conductive paste of the present invention, a dry film using the same, and a cured product thereof are suitable for electronic components such as backlights of liquid crystal displays of portable terminals, personal computers, televisions, etc., and light-emitting elements such as LEDs.
Claims
1. A thermally conductive paste, characterized in that: comprising (A) a thermosetting component, (B) a thermally conductive filler, and (C) a colorant, The amount of the thermally conductive filler (B) blended is 30% by weight or more and 80% by weight or less relative to the total solid content of the thermally conductive paste. The thermally conductive paste was heat-cured at 150° C. for 1 hour to obtain a cured film. The absorbance of the cured film at a measurement wavelength of 364 nm when the film thickness of the cured film is 10 μm is 0.75 or more and 1.50 or less, The L value of the L*a*b colorimetric system when the cured film has a film thickness of 100 μm is 28 or more and 38 or less, The thermal conductivity of the cured film when the film thickness is 100 μm is 0.65 W / m·K or more and 3.1 W / m·K or less.
2. The thermally conductive paste according to claim 1, characterized in that The (A) thermosetting component contains an epoxy resin having at least one structure selected from a biphenyl skeleton and a dicyclopentadiene skeleton.
3. The thermally conductive paste according to claim 1 or 2, characterized in that: The (B) thermally conductive filler includes two or more thermally conductive fillers having different average particle sizes.
4. The thermally conductive paste according to claim 1 or 2, characterized in that: The (B) thermally conductive filler includes a first thermally conductive filler having a small average particle size and a second thermally conductive filler having a large average particle size, and when the average particle size of the first thermally conductive filler is 1, the average particle size of the second thermally conductive filler is 1.5 or more and 5.0 or less.
5. The thermally conductive paste according to claim 1 or 2, characterized in that: The amount of the (A) thermosetting component blended is 10% by weight or more and 70% by weight or less relative to the total solid content of the thermally conductive paste.
6. The thermally conductive paste according to claim 1 or 2, characterized in that: The amount of the colorant (C) blended is 1% by weight or more and 10% by weight or less relative to the total solid content of the thermally conductive paste.
7. The thermally conductive paste according to claim 1 or 2, characterized in that: It also contains (D) thermal conductivity enhancing material.
8. The thermally conductive paste according to claim 7, characterized in that The (D) thermally conductive reinforcing material is present in an amount of 0.1% by weight or more and 2.0% by weight or less based on the total solid content of the thermally conductive paste.
9. A dry film, characterized in that: The present invention comprises a resin layer obtained by applying the thermally conductive paste according to any one of claims 1 to 8 onto a film and drying the film.
10. A solidified product, characterized in that: This is obtained by curing the thermally conductive paste according to any one of claims 1 to 8 or the resin layer of the dry film according to claim 9.
11. An electronic component, characterized in that: A cured product according to claim 10.
Citation Information
Patent Citations
Heat-dissipating epoxy resin composition and insulated electric and electronic component
JP2004010668A
Thermosetting resin composition, cured film, substrate provided with the cured film, and electronic component
CN107207702A
Black photosensitive resin composition
CN111381441A